Relationship between the findings of pure-tone audiometry and otoacoustic emission tests on military police personnel - Guida, Heraldo Lorena; de Sousa, Ariane Laís; Cardoso, Ana Cláudia Vieira (Arquivos Internacionais de Otorrinolaringologia, 2012)
Introduction: Otoacoustic emissions can be an alternative for cochlear evaluation in noise induced hearing loss (NIHL).Objective: To investigate the correlation between the findings of audiometry results and distortion product otoacoustic emissions (DPOAE) in the military police.Method: from cross-sectional and retrospective study, 200 military police officers were submitted to audiological evaluation - pure tone audiometry and DPOAE.Results: considering the provisions of Ordinance 19 of the Labour Department, the results were suggestive of induced hearing loss by high sound pressure levels in 58 individuals, distributed as follows: 28 (48.3%) bilateral cases and 30 (51.7%) unilateral cases, and 15 (25.85%) in each ear. The correlation between the audiometric and DPOAE showed statistical significance in most of the frequencies tested in both ears, confirming that the greater the degree of hearing loss, the smaller the DPOAE amplitudes. In addition, there was observed significant difference between the DPOAEs amplitudes of normal subjects and listeners with hearing loss, confirming the lowering of responses in the group with hearing loss.Conclusion: considering that the correlation between pure tone audiometry and DPOAE, we conclude that otoacoustic emissions can be a complementary tool for the detection and control of NIHL in military police.
Keywords: evaluation; audiometry; police; military personnel